Phase transition induced interfacial debonding in shape memory alloy fiber–matrix system. (1st December 2015) - Chi, Yin; Li, Mingpeng; Xu, Lihua; Sun, Qingping
Abstract: This paper investigates the phase transition induced interfacial debonding of an embedded superelastic NiTi shape memory alloy (SMA) fiber in an epoxy matrix. In situ interfacial debonding morphology and the stress–strain responses of the fiber are obtained for different fiber diameter and surface roughness. It is shown that, depending on these fiber parameters, a ductile or a brittle debonding can occur. The ductile debonding is caused by the phase transition of the fiber and took place together with the propagating necking front of the martensite domain. Compared with the tension of a free-standing fiber, the fiber–matrix bonding can lead to an increase in the front propagating force (plateau) of the fiber. By using Griffith's energy balance approach, the crack surface energy is derived and the predictions of crack driving force agree well with the experimental data.